The identity of the largest enterprises located in Poland and communication of corporate social activities on corporate websites = Tożsamość największych polskich przedsiębiorstw a komunikowanie działań społecznych na korporacyjnych stronach internetowych - Seiler, Bartosz; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
Today's enterprises are becoming more and more socially active. In some respects, they are starting to resemble third-sector organizations. In the context of progressive isomorphism, the issue of organizational identity deserves attention. Identity is based, among others, on organizational mission and values, whose management requires the shaping of coherent links between these components, as well as actual efforts and their communication. Modern enterprises are markedly fond of using electronic media, including corporate websites, to communicate with the audience.
Keywords: tożsamość organizacji; CSR; misja; wartości; strony internetowe korporacji; komunikacja; organizational identity; mission; values; corporate website; communication